Reduction in Methane Productions from Sheep by Supplemented of Moringa oleifera Leaf Extract in The Ration - Wardhana Suryapratama; Fransisca Maria Suhartati (ANIMAL PRODUCTION, 2022)
This study aimed to evaluate the decreasing methane gas production in sheep by supplementing Moringa oleifera extract in the ration. The study was conducted in a Completely Randomized Design with One Way Classification. The treatment of Moringa oleifera extract was offered at 0, 0.25 and 0.50% of DM ration, each with six replicates, which constitutes 18 treatment units. The materials included ruminal fluid of three freshly slaughtered thin-tailed sheep derived from an abattoir in Banyumas Central Java. Moringa oleifera leaves were oven-dried at 60ºC for 2 x 24 h, ground into powder, and extracted using ethanol. The ration consisted of concentrate and ammoniated rice straw with a ratio of 60:40 (DM basis). The concentrate was composed of 2:1 rice bran and coconut meal. The measured variables included total protozoa, methane gas production, total bacteria, N-NH3 concentration, and protein synthesis of ruminal fluid. The result indicated 0.50% Moringa oleifera extract (DM basis) produced the lowest total protozoa, the highest total bacteria and protein microbe synthesis, and the lowest methane gas production.